(untitled) (Medical Forum Monthly, 2024)
Objective: This study was conducted to estimate the seroprevalence of HCV in maintenance hemodialysis patients. Study Design: Experimental prospective study. Place and Duration of Study: This study had been carried out in the Department of Microbiology, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from 1st July, 2010 to 30th April, 2011. Materials and Methods: Irrespective of age and gender 200 samples were collected from the patients on chronic maintenance hemodialysis that at least had 20 cycles of hemodialysis from tertiary care hospital of Karachi. The nature of the sample was 5 cc blood. All the study subjects were briefed about the study program and a written consent form had been signed after getting permission from hospital ethical committee. Diagnosed patients of HCV prior to commencement of hemodialysis and patients who had less than 20 hemodialysis cycles were excluded from this study. Results: Two hundred patients (125 male and 75 females) were between the ages of 30-77 years with mean 56.7±0.68. 29% patients were seropositive for HCV in chronic maintenance hemodialysis patients. According to duration of dialysis, 3.5% were seropositive in whom duration of dialysis was less than 1 year, 18.4% were seropositive in whom duration of dialysis is in between 1.1-2.0 years, 13.3% were seropositive in whom duration of dialysis is in between 2.1-3.0 years, 52.6% were seropositive in whom duration of dialysis is in between 3.1-4.0 years while 61% were seropositive in whom duration of dialysis is more than 4 years. Highly significant statistical difference is observed as the duration of dialysis increases as p-value is highly significant as 0.001 for HCV. Seroprevalence of HCV infection according to schedule of dialysis is insignificant as the p-value is greater then 0.05. Conclusion: This study confirms that HCV infection is a serious and major problem in our hemodialysis units. Duration of dialysis and surgery is directly proportional to the seropositivity, while transfusion was not statistically related to the cause of HCV infections in hemodialysis patients.